Mills on the Frontier: The Water Mills of the Bishopric of Concepción (1550-1650); [Molinos en la Frontera: Los Rodeznos del Obispado de Concepción (1550-1650)] - Lacoste, P (Universidad Pedagogica y Tecnologica de Colombia, 2024)
This article examines the socio-economic characteristics of flour-producing hydraulic mills in the Bishopric of Concepción, southern Chile, from the Spanish colonization period until the mid-17th century. From a social history perspective, the relationship between religious communities and hydraulic mills is analysed. Through sources located in the General Archive of the Indies and the National Historical Archive, eighteen mills were identified in various areas, from the Andalién River to the frontier forts. These mills, like others in colonial America, supplied wheat to cities and consolidated the social status of convents and privileged families. Additionally, unique dynamics were observed in terms of motivations, development, and socio-economic impact, closely linked to the military sphere and reflecting cultural integration in the frontier zone. © 2024 Universidad Pedagogica y Tecnologica de Colombia. All rights reserved.